« Vos pensées ne sont pas mes pensées et mes chemins ne sont pas vos chemins » (Isaïe 55.8) : une réflexion sur le thème de l’ordre dans les Suspiria de Profundis (1845) de Thomas De Quincey - Frédéric Slaby (Revue LISA)
This article looks at the theme of order in Thomas De Quincey’s Suspiria de Profundis (1845). Although chaos is easily noticeable in De Quincey’s digressional style, order is also a recurring motif in the narrative of this mature work. Indeed, for the Protestant and Romantic author plagued by suffering, chaos and order are the starting points for broader reflections. De Quincey discovers that chaos in the outer and inner worlds is but apparent, and that deciphering these worlds enables him to see a unifying or organizing force beneath contraries and paradoxes. As a consequence, in his hermeneutics based on the scandal of suffering, De Quincey introduces the notion of obliqueness operating through the masks behind which God acts, thus retracing the very paths taken by God and disclosing his own theology.